Adhesive Arachnoiditis following Inadvertent Epidural Injection of 2% Chlorhexidine in 70% Alcohol—Partial Recovery over the Ensuing Eight Years. Issue 6 (November 2018) - Iqbal, I. Mohamed; Morris, R.; Hersch, M.
We report a case of serious neurologic injury due to inadvertent epidural injection of 8 ml of the antiseptic 2% chlorhexidine in 70% alcohol during a procedure aimed to relieve the pain of labour. This resulted in immediate severe back pain, progressive tetraparesis and sphincter dysfunction caused by damage to the spinal cord and nerve roots. Subacute hydrocephalus necessitated drainage, but cranial nerve and cognitive function were spared. Magnetic resonance imaging documented marked abnormality of the spinal cord and surrounding leptomeninges. In the ensuing eight years, there has been clinical and electrophysiological evidence of partial recovery, but neurologic deficit remains severe.